2017
DOI: 10.1177/0394632017715837
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: MicroRNA-132 protects hippocampal neurons against oxygen-glucose deprivation–induced apoptosis

Abstract: Hypoxic-ischemic brain injury (HIBI) results in death or long-term neurologic impairment in both adults and children. In this study, we investigated the effects of microRNA-132 (miR-132) dysregulation on oxygen-glucose deprivation (OGD)-induced apoptosis in fetal rat hippocampal neurons, in order to reveal the therapeutic potential of miR-132 on HIBI. MiR-132 dysregulation was induced prior to OGD exposure by transfection of primary fetal rat hippocampal neurons with miR-132 mimic or miR-132 inhibitor. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
(48 reference statements)
4
18
0
Order By: Relevance
“…OGD stimulation often triggers the aberrant miRNAs expression, like miR-7 [41], miR-155 [42], miR-132 [43], miR-27a [21]. Interestingly, Cai et al found that miR-27a overexpression attenuated OGD-induced injury in hippocampal neurons [21], which was consistent with our results.…”
Section: R E T R a C T E Dsupporting
confidence: 91%
“…OGD stimulation often triggers the aberrant miRNAs expression, like miR-7 [41], miR-155 [42], miR-132 [43], miR-27a [21]. Interestingly, Cai et al found that miR-27a overexpression attenuated OGD-induced injury in hippocampal neurons [21], which was consistent with our results.…”
Section: R E T R a C T E Dsupporting
confidence: 91%
“…Consistent with this hypothesis, miR-212/132 were upregulated in the hypoxic human in vitro BBB model, in human post mortem TBI samples as well as in serum exosomes from patients with MHS. Our results are in line with other reports showing hypoxia-induced expression of miR-132 and/or miR-212 in isolated hippocampal neurons, in a model of hindlimb ischemia, and in Schwann cells [4043]. To the authors’ best knowledge, this is the first report showing OGD-mediated induction of miR-212/132 in BMEC.…”
Section: Discussionsupporting
confidence: 93%
“…Prior studies have proposed the notion that miR-132 confers neuronal protection against OGD-induced apoptosis and its upregulation resulted in attenuated cerebral injury in MCAO mice ( Sun et al, 2017 ; Zuo et al, 2019 ). In this study, RT-qPCR results demonstrated that miR-132 expression in MCAO mice was notably downregulated when compared to that in sham-operated mice ( Figure 3A ), whule the expression of miR-132 was notably decreased in OGD-treated neurons when compared to that in normal controls ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%